2020
DOI: 10.1183/23120541.00246-2019
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled corticosteroid withdrawal may improve outcomes in elderly patients with COPD exacerbation: a nationwide database study

Abstract: BackgroundInhaled corticosteroids (ICSs) are used for advanced-stage chronic obstructive pulmonary disease (COPD). The application and safety of ICS withdrawal remain controversial.This study aimed to evaluate the association between ICS withdrawal and outcomes in elderly patients with COPD with or without comorbid bronchial asthma, who were hospitalised for exacerbation.Patients and methodsWe conducted a retrospective cohort study using the Japanese Diagnosis Procedure Combination database from July 2010 to M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Using data from the Clinical Practice Research Datalink (CPRD) in the UK, Oshagbemi et al [ 29 ] did not observe any increase in risk of moderate or severe exacerbations or mortality in a population of + 40,000 COPD patients in primary care irrespective of the blood eosinophil counts. Finally, in a retrospective study on the effect of withdrawal of ICS after hospitalisation for COPD in Japan, Jo et al [ 30 ] observed a reduced incidence of re-hospitalisation for COPD exacerbations or death in patients who withdraw ICS.…”
Section: Discussionmentioning
confidence: 99%
“…Using data from the Clinical Practice Research Datalink (CPRD) in the UK, Oshagbemi et al [ 29 ] did not observe any increase in risk of moderate or severe exacerbations or mortality in a population of + 40,000 COPD patients in primary care irrespective of the blood eosinophil counts. Finally, in a retrospective study on the effect of withdrawal of ICS after hospitalisation for COPD in Japan, Jo et al [ 30 ] observed a reduced incidence of re-hospitalisation for COPD exacerbations or death in patients who withdraw ICS.…”
Section: Discussionmentioning
confidence: 99%
“…We identified the following variables: age; sex; body mass index (BMI) at admission; comorbidities; 18 the Charlson comorbidity index; 19 teaching hospital admission; ICU admission; admission fiscal year; diagnoses; 20 procedures performed on the day of admission; medications used on the day of admission including corticosteroid, and blood product use. BMI (kg/m 2 ) was categorized as <18.5, 18.5–24.9, 25.0–29.9, ≥30.0, or missing data.…”
Section: Methodsmentioning
confidence: 99%
“…JO et al [60] investigated whether withdrawal compared to continuation of ICS was related to worse outcomes in terms of rehospitalisation or death or treatment for new exacerbations. Propensity score analyses were used in a retrospective cohort study of patients aged ⩾65 years who were hospitalised for COPD exacerbation using the Japanese Diagnosis Procedure Combination database from July 2010 to March 2016 [60]. There was a 30% smaller risk of rehospitalisation or death and significantly less exacerbations in the group that discontinued ICS.…”
Section: Maintenance Pharmacotherapymentioning
confidence: 99%